The Influence of Risk Perception, Overconfidence, and Herding Behavior on Investment Decision - Rachel Halim; Ary Satria Pamungkas (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to determine the influence of risk perception, overconfidence, and herding behavior on investment decision. The population of this research is all stock investors who are domiciled in Riau. The sample was selected using purposive sampling method which amounts to 152 respondents. This research method uses Structural Equation Modeling (SEM) with Smart PLS software version 3.2.9. The purpose of this research is that investors can consider their decisions well before making an investment decision and find out how their psychological factors can affect their investment decision. The result of this research is that there is a positive influence of risk perception, overconfidence, and herding behavior on investment decision.